2020
DOI: 10.3389/fbioe.2020.00876
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporotic Goat Spine Implantation Study Using a Synthetic, Resorbable Ca/P/S-Based Bone Substitute

Abstract: One primary purpose of the present study is to clarify whether the highly porous, resorbable Ca/P/S-based bone substitute used in this study would still induce an osteoporotic bone when implanted into the osteoporotic vertebral defects of ovariectomized (OVX) goats, or the newly-grown bone would expectantly be rather healthy bone. The bone substitute material used for the study is a synthetic, 100% inorganic, highly porous and fast-resorbable Ca/P/S-based material (Ezechbone R Granule CBS-400). The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Hydroxyapatite is a major inorganic component in human and animal bones ( Palmer et al, 2008 ; Yang et al, 2020 ). As an important implant and scaffolding material, it has substantial clinical potential in medicine, dentistry, and orthopedics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyapatite is a major inorganic component in human and animal bones ( Palmer et al, 2008 ; Yang et al, 2020 ). As an important implant and scaffolding material, it has substantial clinical potential in medicine, dentistry, and orthopedics.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that incorporating Gd 3+ may enhance MRI capacity of composites, such as Gd NP–diethylenetriaminepentaacetic acid (Gd NPs-DTPA)-terminated dendrimer ( Langereis et al, 2004 ) and Gd ions entrapped in zeolites ( Platas-Iglesias et al, 2002 ). It has been demonstrated that calcium phosphate tribasic materials doped with Gd 3+ exhibited ferromagnetic properties and then contributed to excellent MRI performance ( Shen et al, 2015 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the entire process of bone regeneration of CBS-400 revealed a rapid increase in the proportion of new cancellous bone to over 40% at 4 weeks after implantation, followed by a bone remodeling process toward normal cancellous bone. As much as 85% of the bone substitute had been resorbed about 12 weeks after implantation [ 29 , 33 ]. According to the operation notes from the medical records, we collected fourteen cases of complex intra- and peri-articular fractures with Ezechbone® Granule bone grafting between 2019/11 and 2021/11.…”
Section: Methodsmentioning
confidence: 99%
“…However, the disadvantages of allografts such as the increased risk of disease transmission and ethical issues have led to the adoption of novel bone graft substitutes. With the shortage of donors for transplantation, xenotransplantation has emerged as an alternative option ( Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%